Late Pleistocene and Holocene paleoenvironments in ponds and alluvial sediments of Upper Paraná River, Brazil - Guerreiro, Renato Lada; Stevaux, José Cândido; Parolin, Mauro; Assine, Mario Luis [UNESP] (Sociedade Brasileira de Paleontologia, 2013)
Freshwater sponge spicules were analyzed as a paleoenvironmental proxy indicator in five cores of ponds and alluvial fan sediments in the Upper Paraná River's left bank, near Querência do Norte town, northwestern of State of Paraná, southern Brazil. Two optically stimulated luminescence (OSL) dates were obtained from sediments of ponds and one radiocarbon (14C) date was obtained from the alluvial fan. Microscopic analysis of spicules preserved in the sediments allowed a determination of freshwater sponge species. The species assemblage provides evidence for dominantly dry conditions in the Upper Paraná River during the Late Pleistocene. A wetter climate phase was recognized at 14C 7,540 yrs BP, with alluvial fan formation commencing at the transition of the dry Pleistocene climate to the Early Holocene wet climate. This wet interval was characterized by a sponge assemblage marked by the presence of the Neotropical families and typically associated with lotic environments. Sponge spicules analysis from pond sediments reject the possibility that lotic environments contributed to pond genesis and evolution. © 2013 by the Sociedade Brasileira de Paleontologia.
Keywords: Alluvial fan; Freshwater sponge spicules; Paleoclimate; Paraná River; Ponds; Quaternary